(untitled) (Tanzania Medical Journal, 2022)
Background Head injury is a common presenting condition to most orthopedic and neurosurgical departments in the country. Head injuries are commonly associated with ocular adnexal and globe injuries, which can be visual threatening. Early recognition and intervention for ocular involvement can prevent devastating effects of visual disability and improve overall rehabilitations of affected patients. Currently in Tanzania, there is an increase in the use of motorcycles as a source of employment with a corresponding increase in road traffic accidents and head injuries. The aim of the study was to assess the ocular manifestations in patients with head injury. Methods This was a hospital based descriptive cross-sectional study among adult patients who were admitted at the neuro-surgery department at Muhimbili Orthopedic Institute between October 2019 and January 2020. We consecutively sampled and recruited 147 patients who had sustained head injury within one week. A short history was taken followed by a standard ophthalmological assessment to elicit different ocular manifestations. Data was analyzed using the Statistical Package for Social Sciences version 23 and presented as frequency tables. Chi squared test was used to compare differences between variables and a p-value of less than 0.05 was considered significant. Results A total of 177 patients with head injury were recruited for the study comprising of 147(82%) males. The age range was from 18 to 59 years with a median of 30 (26, 38) years. The commonest causes of head injury were road traffic accidents and assault which involved 117(70.1%) and 29(17.4%) patients, respectively. Ocular manifestations were found in 234 eyes of 117(70%) patients where more than 30% of patients had vision threatening ocular abnormalities. Eyelid ecchymosis and sub-conjunctiva hemorrhage were the commonest mild ocular manifestations. Severe vision threatening ocular manifestations included corneal epithelia defects, papilledema, pupillary abnormalities and orbital fractures. Conclusion Motor traffic accidents and assaults were the leading causes of head injury, where vision threatening ocular involvement is common. Concurrent evaluation and institution of appropriate management of these patients by an ophthalmologist is emphasized to avoid visual disability and improve overall rehabilitation of affected patients.